Ecologia da taxocenose de lagartos na Serra Vermelha, Piauí, Nordeste do Brasil : desvendando padrões de diversidade e uso do recurso em uma área de transição entre os biomas Caatinga e Cerrado - Carvalho, Breno Falcão de (2022)
To be considered structured, species in a community must use the available resources non-randomly. Several factors may be related to the presence of structure, so unraveling the patterns that shape biological communities is in the interest of all ecologists. With the support of the project “Passado, presente e futuro da Caatinga: história, ecologia e conservação da herpetofauna frente às mudanças ambientais” we sampled the herpetofauna of Serra Vermelha (Redenção do Gurguéia – Piauí), a region located in the transitional zone between the Caatinga and Cerrado biomes in the northeastern part of Brazil. Employing lizard assemblage as model organisms, we investigated the patterns of resource use and occurrence of species taking into consideration spatial, climatic, trophic, and morphological parameters, addressing the ecology of the assemblage in two chapters. In the first chapter, we investigated the pattern of resource partitioning by lizards, and the historical/ecological influence on the observed structure. Then, in the second chapter, we evaluated changes in lizard diversity across a environmental gradient at Serra Vermelha.